2011
DOI: 10.1007/s00417-011-1754-1
|View full text |Cite
|
Sign up to set email alerts
|

UVA-riboflavin photochemical therapy of bacterial keratitis: a pilot study

Abstract: This trial illustrates that photosensitization of riboflavin using UVA at 365 nm has the potential to induce healing in patients with microbial keratitis. The results from the treatment of these 16 patients with corneal ulcers indicate that UVA-riboflavin photochemical therapy merits a controlled study in order to assess its efficacy and safety compared to antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
97
1
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 49 publications
(61 reference statements)
11
97
1
12
Order By: Relevance
“…Thus, it increases resistance against microbial degradation and corneal melting (26,(35)(36) . Even though some clinical trials and experimental studies have shown improvement of fungal ulcers with CXL (21,23) , this was not observed in our study. All of our patients with fungal ulcers underwent adjuvant surgical treatment aimed at curing the infectious process.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Thus, it increases resistance against microbial degradation and corneal melting (26,(35)(36) . Even though some clinical trials and experimental studies have shown improvement of fungal ulcers with CXL (21,23) , this was not observed in our study. All of our patients with fungal ulcers underwent adjuvant surgical treatment aimed at curing the infectious process.…”
Section: Discussioncontrasting
confidence: 92%
“…Makdoumi Table 3 Sample distribution according to ulcer size, area, healing time, and culture Table 4 Visual acuity before and after CXL Table 6 Type of culture, complications, and additional surgical procedures this study the lesions healed, with consequent improvement in visual acuity without the need for antibiotic therapy (23) . Martins SA et al studied the in vitro response of Staphylococcus epidermidis, Staphylococcus aureus, and Pseudomonas aeruginosa to CXL.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, research into the development of novel therapeutic approaches is essential. In this regard photodynamic inactivation has been in experimental and clinical use throughout the last decade (6)(7)(8). Research on cystic fibrosis established an antimicrobial effect of gaseous nitric oxide (gNO) in infections with P. aeruginosa using a rat model (9).…”
Section: Introductionmentioning
confidence: 99%